2014
DOI: 10.1111/jvim.12431
|View full text |Cite
|
Sign up to set email alerts
|

Repeatability and Intra‐ and Inter‐observer Agreement of Cervical Vertebral Sagittal Diameter Ratios in Horses with Neurological Disease

Abstract: BackgroundSagittal ratio values (SRVs) of cervical vertebrae are used for ante‐mortem diagnosis of cervical vertebral stenotic myelopathy, but intraobserver and interobserver variability in measurement may influence radiographic interpretation of vertebral stenosis in horses with neurological disease.ObjectivesTo determine intraobserver repeatability in SRVs, intra‐ and interobserver agreement in SRVs and whether or not agreement was influenced by animal age.AnimalsForty‐two horses (>1 year old) with neurologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 27 publications
1
12
0
Order By: Relevance
“…Interestingly, although horses with anomalous C6 were more likely to have an intravertebral sagittal ratio less than 0.5, they were less likely than horses with normal C6 to have neurologic deficits attributable to the cervical region. This highlights the lack of accuracy of the intravertebral sagittal ratio for diagnosis of cervical vertebral stenotic myelopathy . Initially the intravertebral sagittal ratio was reported to have sensitivity and specificity as high as 89% for identification of cervical stenotic myelopathy .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, although horses with anomalous C6 were more likely to have an intravertebral sagittal ratio less than 0.5, they were less likely than horses with normal C6 to have neurologic deficits attributable to the cervical region. This highlights the lack of accuracy of the intravertebral sagittal ratio for diagnosis of cervical vertebral stenotic myelopathy . Initially the intravertebral sagittal ratio was reported to have sensitivity and specificity as high as 89% for identification of cervical stenotic myelopathy .…”
Section: Discussionmentioning
confidence: 99%
“…Both neurologic dysfunction and perceived cervical pain are subjective assessments that vary between individuals . A limitation of the radiographic assessment was the use of the intravertebral ratio, as this measurement has been reported to be unreliable with variation of 5–10% . The main reason for including this parameter in the study was as part of the morphometric study, to refer to parameters commonly used, and not as a diagnostic test.…”
Section: Discussionmentioning
confidence: 99%
“…Also in horses, many studies highlight the controversy, difficulties and limitations of cervical radiography, myeolography, computed tomography (CT), magnetic resonance imaging (MRI) and myeloscopy to diagnose spinal cord disease. Sensitivities (47–50%) and specificities (70–78%) of cervical radiographs and sagittal ratio calculations are too low for adequate diagnosis of spinal cord compression [ 5 , 6 ] and variation between observers is high [ 7 ]. Myelography also has a low sensitivity (43–85%) and additionally requires general anesthesia and intrathecal contrast injection [ 6 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the fact that the value of the intravertebral ratio at the C4/C5 site was lower than 48.5%, and that the intervertebral ratio considered more specific was lower than at C3/C4, which, based on the cited study, could have high diagnostic value, was not confirmed in the measurements performed during the myelography [8, 9]. This may have been caused by differences in the assessment of the cervical radiographs [12]. However, myelography is considered an important intravital diagnostic tool that enables the qualification of patients for cervical vertebral stabilisation surgery, therefore our study focused on the C3/C4 analysis.…”
Section: Discussionmentioning
confidence: 99%